2021
DOI: 10.1186/s13054-021-03588-4
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship between ventilator-associated pneumonia and mortality in COVID-19 patients: a planned ancillary analysis of the coVAPid cohort

Abstract: Background Patients with SARS-CoV-2 infection are at higher risk for ventilator-associated pneumonia (VAP). No study has evaluated the relationship between VAP and mortality in this population, or compared this relationship between SARS-CoV-2 patients and other populations. The main objective of our study was to determine the relationship between VAP and mortality in SARS-CoV-2 patients. Methods Planned ancillary analysis of a multicenter retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
2
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 33 publications
4
52
2
3
Order By: Relevance
“…Once again, the in-hospital course of COVID-19 patients admitted to the ICU is different, with a low reported rate of bacterial co-infection at admission as compared to other causes of viral pneumonitis [ 23 ]. However, recent studies have reported that patients with SARS-CoV-2 infection are at higher risk for ICU-acquired pneumonia [ 24 , 25 ] as compared with other causes of pneumonitis, with some data suggesting a significant association between increased mortality and ICU-acquired pneumonia in severe COVID-19 patients [ 25 ]. However, precise evaluation of the attributable mortality, defined as the percentage of deaths that would not have occurred without infection, is complex for ICU-acquired pneumonia and requires the use of competing risk statistical models.…”
Section: Discussionmentioning
confidence: 99%
“…Once again, the in-hospital course of COVID-19 patients admitted to the ICU is different, with a low reported rate of bacterial co-infection at admission as compared to other causes of viral pneumonitis [ 23 ]. However, recent studies have reported that patients with SARS-CoV-2 infection are at higher risk for ICU-acquired pneumonia [ 24 , 25 ] as compared with other causes of pneumonitis, with some data suggesting a significant association between increased mortality and ICU-acquired pneumonia in severe COVID-19 patients [ 25 ]. However, precise evaluation of the attributable mortality, defined as the percentage of deaths that would not have occurred without infection, is complex for ICU-acquired pneumonia and requires the use of competing risk statistical models.…”
Section: Discussionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified an error in the Abstract and Results section. The correct numbers and text are given hereafter.…”
Section: Correction To: Crit Care (2021) 25:177 Https://doiorg/101186/s13054-021-03588-4mentioning
confidence: 99%
“…All the changes that were requested are implemented in this correction and the original article [ 1 ] has been corrected.…”
Section: Correction To: Crit Care (2021) 25:177 Https://doiorg/101186/s13054-021-03588-4mentioning
confidence: 99%
“…The main factors associated with mortality during VAP are septic shock and severe acute respiratory syndrome (ARDS). However, features and specific risk factors of VAP in COVID-19 patients have not yet been established [ 13 ].…”
Section: Introductionmentioning
confidence: 99%